Studi Tentang Tata Ruang Kantor Pada Unit Pengelolaan Uang Rupiah Di Kantor Perwakilan Bank Indonesia Provinsi Kalimantan Timur - Johan Lucas Away; Norhayadi Norhayadi (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2021)
In modern times like today, office activities are growing and are required to be fast and precise, therefore the role of office layout is very influential on the effectiveness of office employees, but currently office layout is still receiving less attention, both in government agencies and companies. -private companies that have an impact on the performance of office employees who have not been maximized and have not been effective. The purpose of this research is to study whether the office layout of the Rupiah Money Management section at the Samarinda branch of the Bank Indonesia Representative Office has the correct layout. The results of this study indicate that the existing office layout in the Rupiah Money Management Unit at the Bank Indonesia Representative Office in East Kalimantan Province is not in accordance with the principles of good office layout.